A new vision for Federal information technology procurements. (September 2015) - Rung, Anne; Blum, Mathew
This article highlights several of the most impactful challenges that have plagued IT acquisitions over the last two decades and describes transformative initiatives that the Obama Administration's Office of Federal Procurement Policy (OFPP) announced last December to help agencies overcome long-standing obstacles and get better results for the taxpayer. The discussion looks separately at IT commodity spend and IT systems investments, as smarter IT buying requires an understanding of these differences and solutions that are targeted to change long-standing cultural and structural assumptions that have prevented real and sustained progress in the past.